A literature review of current surgical treatment for congenital pseudoarthrosis of the tibia - Panji - Sananta; Ade Yahya Nasution; Eka Noviya Fuzianingsih (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2024)
Congenital pseudarthrosis of the tibia (CPT) is an infrequently observed condition. However, it is considered to be one of the most complex ailments in the field of pediatric orthopedics. In cases where a tibial fracture is absent, the conventional treatment approach involves using bracing as a preventive measure against fractures. Various surgical modalities have been proposed for the management of CPT, including intramedullary (IM) rod fixation, external fixators, on-lay grafts, cancellous grafts, periosteal grafts, Paley cross-union, amputation, vascularized fibula grafts, and induced membrane techniques. These modalities can be used in different combinations and permutations. The need for repetitive surgical interventions due to unsuccessful therapeutic outcomes or modifications in secondary treatments can significantly disrupt the childhood experience, resulting in prolonged and recurrent functional limitations. In certain instances, amputation may be required as a primary or secondary treatment modality. This literature review will clarify the current surgical interventions for CPT disease based on a summary of research data. The surgery the patient receives significantly impacts their general health and capacity to heal.